Identitäten im Prozess Region, Nation, Staat, Individuum - Horatschek, Anna Margaretha; Pistor-Hatam, Anja (Abhandlungen der Akademie der Wissenschaften in Hamburg, 2015)
Collective identities - national, regional, local, religious, linguistic - are all constructed as opposed to an "other" which is constructed in alterity. They are established by historiography, art, and media. The contributions in this volume analyze characteristics and strategies of European and non-European identity discourses.